Human-Machine Cooperative Decision Making - Rothfuss, Simon (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
The research reported in this thesis focuses on the decision making aspect of human-machine cooperation and reveals new insights from theoretical modeling to experimental evaluations: Two mathematical behavior models of two emancipated cooperation partners in a cooperative decision making process are introduced. The model-based automation designs are experimentally evaluated and thereby demonstrate their benefits compared to state-of-the-art approaches.